Site Soil-Fertility and Light Availability Influence Plant-Soil Feedback - McCarthy-Neumann, Sarah; Kobe, Richard K. (Frontiers in Ecology and Evolution, 2019)
Negative plant-soil feedback (PSF), where plant performance is reduced in soils conditioned by conspecifics, is widely documented in plant communities. However, the strength and sometimes direction of PSF can vary widely, presumably not only due to the plant species within the community but also to environmental context. We hypothesized that soil fertility and light availability influence the direction and strength of plant-soil feedback experienced by tree seedlings. We conducted a 10-week greenhouse experiment and assessed survivorship of Northern red oak (Quercus rubra) and black cherry (Prunus serotina) in low ( 1% full sun) vs. high ( 18% full sun) light availability and in non-sterile vs. sterile soils collected under the canopy of conspecific vs. heterospecific adult trees at five sites that vary in nutrient availability in Manistee National Forest, Michigan, USA. Q. rubra seedlings experienced neutral plant-soil feedback regardless of light level or site as only one seedling died during the course of the experiment. Prunus serotina seedlings experienced microbe-mediated negative PSF in low fertility sites but positive feedback at high fertility sites, but these feedbacks occurred only under high light availability. Consistent with these results, microbe-mediated negative PSF increased with soil Fe3+ and C:N ratios and decreased with NH4+. Our results demonstrate the important role of environmental context, specifically light and soil nutrient availability, on the magnitude and direction of conspecific plant soil feedback, particularly in P. serotina. Since Q. rubra experienced neutral microbial PSF, P. serotina has a relative disadvantage to Q. rubra under lower site fertility, but a relative advantage under higher site fertility. These results are consistent with these species relative abundances in the field and thus PSF could be an important driver of plant community dynamics.